2019
DOI: 10.28991/cej-2019-03091418
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vertical Loads and the Pile Shape on Pile Group Response under Lateral Two-Way Cyclic Loading

Abstract: This paper is presented the lateral dynamic response of pile groups embedded in dry sand under influence of vertical loads and the pile shape in-group, which are subjected to the lateral two-way cyclic loads. The laboratory typical tests with pile groups (2×1) have an aluminum-pipe (i.e. circular, square) pile, embedded length to diameter of pile ratio (L/D=40) and spacing to diameter ratio (S/D) of 3, 5, 7 and 9 are used with different cyclic-load ratio (CLR) 0.4, 0.6 and 0.8. The experimental results are rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The results showed that an increase in the lateral resistance in the group of square piles compared to a circular pile under pure loading conditions within the group (1 × 2), (2 × 1) and (2 × 2) about (16%, 20% and 23%) respectively. Whereas this proportion increases by (30%) under combined loads for groups (1×2) and (2×1) and about (10%) for a group (2×2) These results agree with the study presented by [14], [15], [16] and [8].…”
Section: Effect Of Cross-sectional Shape Of Pile On Piled Raftsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that an increase in the lateral resistance in the group of square piles compared to a circular pile under pure loading conditions within the group (1 × 2), (2 × 1) and (2 × 2) about (16%, 20% and 23%) respectively. Whereas this proportion increases by (30%) under combined loads for groups (1×2) and (2×1) and about (10%) for a group (2×2) These results agree with the study presented by [14], [15], [16] and [8].…”
Section: Effect Of Cross-sectional Shape Of Pile On Piled Raftsupporting
confidence: 92%
“…In fact, piles are exposed to vertical and lateral loads at the same time, so it is important to distinguish the piles behavior in these situations [2]. Many researchers conducted analytical and experimental studies of piled raft foundations and studied the effect of several parameters on their behavior [3]and [4], whereas there are limited experimental studies are available that show the distribution of load within a pile group and studying the effect of spacing [5], [6]and [7] and cross-sectional shape [8] subjected to twoway cyclic lateral loading. However, the results of these studies show that the average load on a pile in a closely spaced group (three pile diameters or 3-D center-to-center distance) is much less than that of a single insulated pile with the same deflection, and the front (leading) row piles in the group carry significantly higher loads than the following row piles at the same deflection.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the cyclic action reduced the soil reaction between the rows of piles. In other hand, the shadowing effect caused the leading piles to disrupt the soil between the rows this also recommended by (7) .…”
Section: Estimate the Maximum Bending Moments For Different Clrmentioning
confidence: 99%
“…Such lateral cyclic loads on piles induced the reversal of stresses in the nearby soils, resulting in progressive degradation in strength and stiffness, which in turn caused a reduce in pile capacity with considerable irreversible deformation, resulting in failure in major situations. (6) Another study which is carried out by Mahmoud and Abbas (7) , states that the group piles were exposed to cyclic and vertical loading to illustrate the effect of the cyclically load ratio (CLR) on the behavior of piles. The findings showed that the lateral movement of the pile's head varied with the cyclically loaded ratio (CLR), before settling in a more consistent pattern, as the number of cycles increased.…”
Section: Introductionmentioning
confidence: 99%
“…The ABAQUS finite element software is used to show the numerical simulation model to investigate the influence of horizontal component of inclined load on pile group and noticed Inclined load, embedded depth of pile cap, and eccentricity of the column are commonly influenced to improve the force of pile group [12]. Another researcher studied the influence of vertical loads on the pile group to lateral displacement [13].…”
Section: Introductionmentioning
confidence: 99%